Universal Screening for Thyroid Disorders in Pregnancy: Experience of the Czech Republic - Potlukova, Eliska; Jiskra, Jan; Telicka, Zdenek; Springer, Drahomira; Limanova, Zdenka (IntechOpen, 2012)
None